Acupuncture Improves White Matter Perfusion and Integrity in Rat Model of Vascular Dementia: An MRI-Based Imaging Study - Ma, Si-Ming; Wang, Lu; Su, Xin-Tong; Yang, Na-Na; Huang, Jin; Lin, Lu-Lu; Shao, Jia-Kai; Yang, Jing-Wen; Liu, Cun-Zhi (Frontiers in Aging Neuroscience, 2020)
White matter lesions induced by chronic cerebral hypoperfusion are associated with cognitive impairment in vascular dementia (VaD). Previous studies showed that acupuncture can ameliorate the cognitive deficits of individuals with VaD. However, the neuroimaging mechanisms of acupuncture on white matter perfusion and integrity remain elusive. In the present study, VaD was induced by bilateral common carotid arteries occlusion (BCCAO) in rats. Morris water maze (MWM) was used to evaluated the spatial learning and memory of rats. Arterial spin labeling imaging and diffusion tensor imaging (DTI) were performed to measure the cerebral blood flow (CBF) and the white matter integrity. Pathological staining was also applied to detect the myelin loss and neuroinflammation. The results demonstrated BCCAO rats with declined CBF exhibited worse MWM performance and altered DTI parameters including decreased fractional anisotropy, elevated radial diffusivity and axial diffusivity in white matter regions. Acupuncture ameliorated cognitive impairment, increased CBF, and protected the myelin sheath integrity but not axons. This protective effects of acupuncture on white matter is significantly correlated with improved CBF. Pathological examination confirmed that the loss of myelin basic protein and microglial activation were attenuated by acupuncture treatment. Our findings suggest that acupuncture protects cognitive function of BCCAO rats through improving white matter perfusion and integrity.